Duração do aleitamento materno e o excesso de peso - Minossi, Vanessa (2013)
Introduction: Overweight has been considered a serious nutrition deviation, becoming a public health problem. Breast milk, to be the most appropriate food for children up to 6 months, may be related to nutritional status in early childhood. Objective: Investigate the prevalence of overweight and its association with the breastfeeding duration. Methods: A cross-sectional study with 106 preschool children from Porto Alegre / RS. Anthropometric and nutritional status classification were carried out. Chi-square test and Kaplan-Meier plot were used to assess breastfeeding (BF). Results: In the sample 55.6% (59) were boys. The classification of nutritional status was performed according to the Z-score ratio W/A, W/S and BMI/A, and the prevalence of overweight was 9.4% (10), 36% (36) and 38.7 % (41), respectively. Related to breastfeeding, 69.8% (74) received BF until 6 months. It was observed that 38.6% (41) of preschoolers who discontinued early exclusive breastfeeding (EBF ≤ 6 months) were overweight, verifying excess frequency higher (40%, n = 2) between those that did not interrupted. In relation to overweight among children who stopped breastfeeding early, there was often higher frequency (45.2%, n = 19) among those who did not interrupt, without statistical significance between the duration of EBF and BF and overweight. Conclusion: Although this study did not find association between breastfeeding duration and overweight, cohort studies with larger samples should be conducted to confirm this finding.